Optimalisasi Transaksi Melalui E-Commerce Sebagai Upaya Peningkatan Penerimaan Pajak - Mohammad Agus Mustam, Andi; Ismiyanto; Muhtarom, M. (Fakultas Hukum Universitas Mulawarman, 2024)
This study aims to address the implementation issues of optimizing transactions through e-commerce as a means to increase tax revenue, as well as the obstacles in implementing these optimization policies. The perspective supporting tax imposition on all e-commerce businesses marketing their products in Indonesia is based on the principle of fairness in tax collection, which should be applied equally to all businesses within the same industry. However, the tax authority's stance on imposing taxes on e-commerce activities has faced objections from local businesses, who argue that taxing this infant industry could hinder the growth and development of e-commerce in Indonesia, as it is still in need of protection. This empirical study collects primary data from various marketplace platform providers in the Surakarta region, with a focus on businesses categorized as MSMEs. The findings indicate that the implementation of e-commerce transaction optimization policies to increase tax revenue has not been comprehensively executed in line with the coverage stipulated by legislation and the technical application of tax policies. Obstacles to policy implementation include regulatory substance issues that necessitate an expansion of tax zoning for e-commerce and a lack of outreach and support for taxpayers.